Eksistensi Taqlid dalam Konteks Pengalaman Keagamaan di Era Kontemporer - Mubarak Mubarak; Nur Resky Aulia; Kurniati Kurniati (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The practice of taqlid is part of the Islamic legal tradition which has an important role in maintaining legal consistency and stability during the classical period. However, in the context of modern times, the practice of taqlid faces various problems, such as legal rigidity, madhhab fanaticism, and excessive dependence on ulama. The subject of this research focuses on the nature and law of taqlid as well as the existence of taqlid and Islamic law in the contemporary era. This research uses a type of normative research, a qualitative approach with a literature review method that involves searching, collecting and in-depth analysis of various references from books and scientific journals. This reference specifically discusses reflections on ushul fiqh in the context of taqlid, including related issues. The results of the research show that taqlid is divided into two according to the ulama, there are those that are forbidden or not allowed and there are also those that are permitted. Because basically taqlid is haram, but we see a phenomenon in society, that not all people can perform ijtihad on their own, so scholars divide two types of taqlid, namely those that are forbidden and those that are obligatory. It is haram for people who are capable of ijtihad but obligatory for ordinary people. Therefore, there needs to be an effort to improve religious education that emphasizes the ijtihad method, as well as encouraging the renewal of Islamic law that is relevant to current developments. In this way, taqlid can be carried out in a moderate and balanced manner, while still opening up space for dynamic and contextual ijtihad.